Barriers and facilitators to the diagnosis of HIV and other STIs in primary care within publicly funded healthcare systems: A systematic review of qualitative studies - Pilar Galicia; Maria Jesús García de Yébenes; Consuelo Pascau; Juan Cuadros González; Loreto Carmona; Jose-Manuel Ramos-Rincón (PLoS ONE, 2026)
Background Human immunodeficiency virus (HIV) and other sexually transmitted infections (STI) are a major public health concern. Primary care (PC) is the ideal setting for their diagnosis. Designing effective strategies requires a thorough understanding of the problems these patients face when seeking care. Objectives To identify barriers and facilitators to the diagnosis of HIV and STIs in PC and classify them according to the theoretical Capability, Opportunity, and Motivation model of Behaviour (COM-B model). The review’s findings will inform the development of specific intervention strategies. Methods We conducted a systematic review (SR) of qualitative studies of barriers and facilitators to the diagnosis of HIV/STI. A systematic literature search, without publication date limitation, was performed in Embase, Cochrane Library, and Medline via PubMed. The Joanna Briggs Institute (JBI) scale was used to assess the risk of bias of the included studies. The results were synthesised and presented according to the dimensions of the COM-B model. Results Of the 1,366 records from the initial search strategy, 70 articles met all inclusion criteria, covering all HIV/STIs and different risk groups. Barriers and facilitators to diagnosis were identified at three levels: patients, professionals, and health system. Patient barriers included confidentiality issues, lack of risk perception, shame and stigma, and access. The barriers at the level of professionals were lack of training, time constraints, and scarcity of resources. Among the facilitators, the most notable were minimally invasive sampling methods, ensuring confidentiality, standardisation of tests, fast and efficient entry points, and professional training. Discussion This SR provides information on barriers and facilitators to HIV/STI diagnosis in PC and across the different stakeholders involved (patients, providers, system). The results are grouped into the different dimensions of a behavioural model (capability, opportunity, and motivation). A thorough understanding of the complexity of the behaviour of people diagnosed with HIV/STIs and all those involved in their management will enable the development of effective intervention strategies to diagnose and prevent these processes, thereby reducing the associated disease burden. Registration: International Prospective Register of Systematic Reviews (PROSPERO: CRD42023404578).